2002
DOI: 10.1097/00007890-200210150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunohistochemical characterization of the onset and resolution of human renal allograft ischemia-reperfusion injury

Abstract: BACKGROUND Following allotransplantation, renal ischemia-reperfusion (I/R) injury initiates a series of events that provokes counter-adaptive immunity. Though T cells clearly mediate allospecific immunity, the manner in which reperfusion events augment their activation has not been established. In addition, comprehensive analysis of I/R injury in humans has been limited. METHODS To evaluate the earliest events occurring following allograft reperfusion and gain insight into those factors linking reperfusion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
59
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 32 publications
8
59
0
Order By: Relevance
“…8 The lack of relation to the number of HLA compatibilities suggests that this cellular influx does not seem to involve an immunological phenomena. This is in accordance with the study of Dragun et al who, in the rat, performed renal biopsies after syngeneic and allogeneic renal transplantation with and without immunosuppression and found no significant differences, 11 and with the findings Hoffman et al 7 and Koo et al 8 in postreperfusion renal biopsies in the clinical setting. Cellular vacuolization is known to occur in renal tubular cells after reperfusion 7 and Katz et al 12 considered urothelial vacuolization to be a sign of rejection of the ureter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…8 The lack of relation to the number of HLA compatibilities suggests that this cellular influx does not seem to involve an immunological phenomena. This is in accordance with the study of Dragun et al who, in the rat, performed renal biopsies after syngeneic and allogeneic renal transplantation with and without immunosuppression and found no significant differences, 11 and with the findings Hoffman et al 7 and Koo et al 8 in postreperfusion renal biopsies in the clinical setting. Cellular vacuolization is known to occur in renal tubular cells after reperfusion 7 and Katz et al 12 considered urothelial vacuolization to be a sign of rejection of the ureter.…”
Section: Discussionsupporting
confidence: 92%
“…6 In this study, the detection of lymphocytes in the urothelial fragments obtained before reperfusion may be related to the fact that the donors were dead, in concordance with the work of Hoffman et al 7 and of Koo et al, 8 who observed higher cellular infiltration in renal biopsies from cadaveric donors compared with living donors. The inverse relationship between mechanical ventilation length and intensity of cellular infiltration may be related to the fact that mechanically ventilated trauma patients, after an initial rise in the immune response, show a decline, affecting mainly cellular immunity.…”
Section: Discussionsupporting
confidence: 90%
“…Monocytes are drawn to an allograft to some extent in proportion to the degree of reperfusion injury (17). The critical requirement of this cell type for T cell activation described herein helps explain the marked augmentation of alloimmunity that occurs commensurate with aggressive reperfusion injury and monocyte graft infiltration after T cell depletion (16).…”
Section: Discussionmentioning
confidence: 81%
“…ECs have been shown by many investigators to induce CD4 ϩ T cell proliferation under certain in vitro conditions, specifically when the cells are preincubated with IFN-␥ 2 (43)(44)(45)(46). However, this condition is not consistent with the physiological absence of IFN-␥ at the time of initial monocyte contact with allogeneic EC posttransplant reperfusion (17) and, thus, may not reflect the most likely conditions present during transplantation. Although CD8 ϩ T cells have been shown in vitro to provide IFN-␥ and to stimulate the proliferative capacity of ECs (40), we have shown in humans via serial protocol biopsies that CD8 ϩ T cells are rare in the early infiltrates of renal allografts in depleted hosts (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation